Pengaruh Pemberian Media Intervensi “Isi Piringku” terhadap Asupan Energi, Zat Gizi Makro dan Pertambahan Berat Badan Ibu Hamil: The Influence of the “Isi Piringku” Intervention Media on Energy Intake, Macro Nutrient Intake, and Weight Gain in Pregnant Women - Achmad, Satriani; Joto, Nur Abri (Fakultas Farmasi, Universitas Mulawarman, Samarinda, Indonesia, 2025)
Nutrition is a fundamental need that is very important for humans; it is essential for sustaining life and serves as fuel for various bodily processes to achieve a quality life. This research aims to determine the effect of the